2010
DOI: 10.1155/2010/357387
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Goldmann Applanation Tonometry and Dynamic Contour Tonometry following Trabeculectomy

Abstract: Background. To evaluate differences between Goldmann Applanation Tonometry (GAT) and Dynamic Controur Tonometry (DCT) following trabeculectomy. Methods. Thirty eight glaucomatous eyes with a history of trabeculectomy (Trabeculectomy group, TG), 20 eyes without a history of trabeculectomy but with a history of latanoprost use (Latanoprost group, LG), and 19 nonglaucomatous eyes (Control group, CG) were included. GAT-IOP, DCT-IOP, the difference between them (dIOP), the central corneal thickness (CCT), the axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…By creating a partial-thickness scleral flap, ocular biomechanical properties might change significantly. Detorakis et al [66] reported a greater difference between GAT and DCT IOP measurements following trabeculectomy versus IOP-matched untreated eyes. Other surgical interventions possibly influence OPA by inducing changes in OR.…”
Section: Opa and Glaucomamentioning
confidence: 99%
“…By creating a partial-thickness scleral flap, ocular biomechanical properties might change significantly. Detorakis et al [66] reported a greater difference between GAT and DCT IOP measurements following trabeculectomy versus IOP-matched untreated eyes. Other surgical interventions possibly influence OPA by inducing changes in OR.…”
Section: Opa and Glaucomamentioning
confidence: 99%